Β-SITOSTEROL: ISOLATION FROM MUNTINGIA CALABURA LINN BARK EXTRACT, STRUCTURAL ELUCIDATION AND MOLECULAR DOCKING STUDIES AS POTENTIAL INHIBITOR OF SARS-CoV-2 Mpro (COVID-19) - CHAUDHARI, RAKESH N; L.KHAN, SHARUK; CHAUDHARY, RAVINDRA S; JAIN, SHIRISH P; SIDDUQUI, FALAK A (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objecive: A novel human coronavirus (HCoV), labelled as SARS-CoV-2 (COVID-19), causing pneumonia is spreading around the world. At present, there are no specific treatments for COVID-19. β-sitosterol is well known for its multiple biological actions. The aim of this research is to isolate and study binding affinity of β-sitosterol for SARS-CoV-2 (COVID-19) main protease (Mpro). Methods: Extraction and Column chromatography was performed to isolate the β-sitosterol from n-hexane extract of Muntingia calabura bark followed by thin layer chromatography (TLC), HPTLC, FTIR and UV-Visible Spectroscopy. The molecular docking studies were performed on SARS-CoV-2 Mpro to determine the binding affinity of the β-sitosterol by using PyRx Virtual Screening Tool. Results: In present study, preliminary phytochemical screening showed presence of carbohydrate, steroid, terpenoid and flavonoid compounds. Total 115 fractions were collected from column chromatography by using benzene as solvent by isocratic elution technique. HPTLC Fingerprinting analysis showed the presence of β-sitosterol under 366 nm. FTIR characterization was performed of the same fraction which clearly gives the absorption peaks which resembles to β-sitosterol structure. Conclusion: The overall study concludes this method can be considered as a standard method for isolation of β-sitosterol from Muntingia calabura bark. Favipiravir have less binding affinity i.e. -5.7 kcal/mol than β-sitosterol which has -6.9 kcal/mol. The no. of hydrogen bonds formed by the Favipiravir is much more i.e. 04 than β-sitosterol which formed only 01 hydrogen bond with SARS-CoV-2 Mpro.